IDIOMS WITH COMPONENT ‘NERVE’: (CZECH-MACEDONIAN PARALLELS) (Journal of Contemporary Philology, 2020)
Idioms in the Czech and in the Macedonian language take a very important part of the lexicological fund of the language. They do not only reflect the life wisdom and experience, but they also show the human capability to create images and games with words, which can indicate not only the development of the language, but also the development of the mentality of a certain nation. They enrich the language and interpersonal communication significantly, which is the basis of mutual familiarization with the people from all around the world. For the purposes of this paper, the material to the Czech works translated intoMacedonian has been analyzed only. Out of that material phrases have been excerpted, those that contain the human body part - ‘nerve’. Then, based on the language material, the analysis was performed into several directions: 1) in regard to their semantics (according to the concept of cognitive theory); 2) in regard to their structure (noun, verb, comparative clauses and whole sentence); and 3) in regard to how they have been translated into Macedonian.
Keywords: Somatic Idioms; Macedonian language; Czech language; Cognitivism; Translation